V1 and V2b interneurons secure the alternating flexor-extensor motor activity mice require for limbed locomotion - Zhang, Jingming (2014)
The reciprocal activation of flexor and extensor muscles constitutes the fundamental mechanism that tetrapod vertebrates use for locomotion and limb-driven reflex behaviors. This aspect of motor coordination is controlled by inhibitory neurons in the spinal cord; however, the identity of the spinal interneurons that serve this function is not known. Here we show that the production of an alternating flexor-extensor motor rhythm depends on the composite activities of two classes of ventrally-located inhibitory neurons, V1 and V2b interneurons (INs). Abrogating V1 and V2b IN-derived neurotransmission in the isolated spinal cord results in a synchronous pattern of L2 flexor-related and L5 extensor-related locomotor activity. Mice lacking V1 and V2b inhibition are unable to articulate their limb joints and display marked deficits in limb-driven reflex movements. Taken together, these findings identify V1- and V2b-derived neurons as the core interneuronal components of the limb central pattern generator (CPG) that coordinate flexor-extensor motor activity.